Vulnerability Scanning of University Computer Network Using Zenmap - Chhillar, Kismat; Shrivastava, Saurabh (Indian Journal of Computer Science, 2021)
University computer networks have become vast and deal with a lot of critical and sensitive data. This demands the university network to be highly secure. To attain network security, timely assessment of network vulnerabilities has become highly indispensable. The vulnerabilities need to be discovered and removed at the earliest as these can be exploited by attackers having malicious intent. To identify network vulnerabilities, various vulnerability scanning tools are available. The present paper deals with an open source tool ZENMAP which is completely free to use. ZENMAP is the GUI (Graphical User Interface) of Nmap. ZENMAP runs Nmap in the background. Nmap (Network Mapper) is a powerful tool to gather information about any network and its individual devices. This paper describes the implementation of ZENMAP on a few hosts of Bundelkhand University computer network to gather necessary information about the hosts. After knowing the loopholes in a host, measures can be taken to remove the loopholes and enhance network robustness and security.